The Relationship Between Employee Voice and Organizational Effectiveness Becomes Significant with The Mediation of Work Engagement - Deppi Andam Dewi; Budi Prasetyo; Doddy Setiawan (Puslatbang KDOD Lembaga Administrasi Negara, 2023)
The best human resource (HR) management practices organizations implement worldwide are still being discussed. One of the causes is a lack of understanding of the decision-making process. Management must develop a strategy for generating constructive ideas and receiving employee feedback to manage the organization effectively. This study aims to understand the mediating effect of work engagement on employee voice and organizational effectiveness with a social exchange approach. One hundred ninety-three employees of Statistics Indonesia were used to assess the hypothesis. The technique used in this study was purposive sampling. To collect data using Google Forms. The results show that employee voice has no direct effect on organizational effectiveness but has a positive and significant impact after being mediated by work engagement. For practical implications, practitioners need to strengthen the employee's voice mechanism by providing opportunities for employees to voice their opinions by feeling heard. Employees will be motivated to become more engaged in their work to increase their effectiveness.